If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 22 = 7y + 5(y + 2) Reorder the terms: 22 = 7y + 5(2 + y) 22 = 7y + (2 * 5 + y * 5) 22 = 7y + (10 + 5y) Reorder the terms: 22 = 10 + 7y + 5y Combine like terms: 7y + 5y = 12y 22 = 10 + 12y Solving 22 = 10 + 12y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-12y' to each side of the equation. 22 + -12y = 10 + 12y + -12y Combine like terms: 12y + -12y = 0 22 + -12y = 10 + 0 22 + -12y = 10 Add '-22' to each side of the equation. 22 + -22 + -12y = 10 + -22 Combine like terms: 22 + -22 = 0 0 + -12y = 10 + -22 -12y = 10 + -22 Combine like terms: 10 + -22 = -12 -12y = -12 Divide each side by '-12'. y = 1 Simplifying y = 1
| 0=x^3-7x+7 | | 5a+5=78 | | 15=.5y | | 5(2y-4)=1 | | 14m+9-6m= | | 7-3x=(-4)x+13 | | x+12x=30,720.00 | | 0,20=((X*2/100*5)-x) | | 0.05(80)+0.4x=0.2(80+x) | | -9(x+5)=3(x+23) | | x+12x=30,720 | | 3x/10=24/9 | | 3(2)-9=5(2-3) | | 49x^2+168x+144=0 | | -9x-35=3x-69 | | 1=y-2x+5 | | 0.05(80)+0.4=0.2(80+x) | | -9x+-35=3x-69 | | -3(-12+4y)+12y=36 | | 23y-22y-8=-11 | | 14-x=1/2 | | -6=4-(8-z) | | ln(x+4)-2lnx=5 | | 7a-3=2a-20 | | 6x+54=4x+70 | | (2x^2+5x-3)(2x+1)= | | 1-5+(-9)-7-13= | | 28x+13=9x+2 | | f(10)=3x+24 | | 28-12.12=s | | -3x+12y=36 | | 6u^2+3u-84=0 |